2019
DOI: 10.3389/fpsyg.2019.00357
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Neural Signals of Disorder and Order Perception

Abstract: Order and disorder are prevalent in everyday life, yet little is known about the neural real-time processing that occurs during the perception of disorder relative to order. In the present study, from a cognitive perspective, by adopting the ERP method, we aimed to examine the elicited real-time neural signals of disorder and order perception when participants processed physical environmental and basic visual disorder and order pictures in an irrelevant red or green rectangle detection task, and we attempted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 52 publications
(82 reference statements)
2
6
0
Order By: Relevance
“…Bertamini et al (2013) proved that randomness patterns have lower perceptual fluency than regular/symmetry patterns. Our recently published event-related potential study examined the neural signals of the disorderly and orderly pictures used in the current Experiments 1 and 2 and supports this assertion that orderly perception is more fluent than disorderly perception (Li et al, 2019). Therefore, on the basis of the above findings, the increased processing fluency generated from the primed orderly pictures may lead to participants' choice of global perceptual processing, whereas the disfluency experienced by the primed disorderly pictures supports participants' choice of local perceptual processing.…”
Section: Discussionsupporting
confidence: 77%
“…Bertamini et al (2013) proved that randomness patterns have lower perceptual fluency than regular/symmetry patterns. Our recently published event-related potential study examined the neural signals of the disorderly and orderly pictures used in the current Experiments 1 and 2 and supports this assertion that orderly perception is more fluent than disorderly perception (Li et al, 2019). Therefore, on the basis of the above findings, the increased processing fluency generated from the primed orderly pictures may lead to participants' choice of global perceptual processing, whereas the disfluency experienced by the primed disorderly pictures supports participants' choice of local perceptual processing.…”
Section: Discussionsupporting
confidence: 77%
“…The trial ended with an inter-trial gray screen that lasted for a random time ranging from 5 – 6 s. Participants were instructed to look at and to pay attention to the images without providing any response; because, later in the session, they would be asked some questions about them. TMS pulses were delivered at 320 ms after image onset, which is consistent with the previously stated evidence that identified an event-related difference between the disorder and order conditions in the N2 component peaking within the 240–350-ms interval (Li et al, 2019). Ordered, disordered, and scrambled versions of the images were presented in random order.…”
Section: Methodssupporting
confidence: 69%
“…However, as mentioned in the introduction, previous research results revealed that people were more likely to abstractly interpret the world when they experienced cognitive disfluency or difficulty than when they experienced cognitive fluency (Alter and Oppenheimer, 2010). If we were to adopt this processing fluency view, together with the aforementioned association of processing fluency with order perception and processing disfluency with disorder perception (Kotabe, 2014; Kotabe et al, 2016; Li et al, 2019), our study 1 should have found that people tended to associate orderly words with low-level construal words and disorderly words with high-level construal words. However, the results showed the opposite pattern: orderly words were more likely to be linked with high-level construal words than with low-level construal words, and the disorderly words were more likely to be connected with low-level construal words than with high-level construal words.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, processing fluency was identified as the underlying mechanism that motivates spontaneous inferences of psychological distance. Behavioral and ERPs studies in disorderliness and orderliness proposed and demonstrated that perceived disorder, compared to perceived order, was cognitively processed more disfluently (Kotabe, 2014; Kotabe et al, 2016; Li et al, 2019). Therefore, the disorderly words used in the current study might have triggered cognitive disfluency, and then this disfluency processing created a distant feeling for the disorderly words, whereas the orderly words had the opposite effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation